Efektifitas Pemberian Terapi Musik terhadap Tingkat Kecemasan Pasien Pre Operasi Sectio Caesarea - Ahmad Zainullah; Anik Enikmawati; Sri Handayani; Safira Dwi Latifah (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Childbirth is a task for a woman or mother that must be faced with fortitude, although they often feel anxious in facing childbirth. There are two ways in the process of normal or natural childbirth and childbirth by cesarean section or often also called cesarean section or sectio caesaria. to determine the effectiveness of providing music therapy on the level of anxiety pre-operative sectio caesarea. The design used in this study was using Quasi Experiment with a one group Pretest and Posttest approach. The number of samples was 20 with the Wilcoxon statistical test. The level of anxiety before giving music therapy in the severe category was 19 people (95%) and the moderate category was 1 person (5%), 2. While for the level of anxiety after giving music therapy in the moderate category 3 people (15%), the mild category 15 people (75%) and the category of no anxiety 2 people (10%). The results of the difference test before and after music therapy on the level of anxiety of pre-operative sectio caesarea patients with a p-value of 0.000 (p <0.05). Music therapy is effective for anxiety in pre-operative caesarean section patients.